AdvantAGE: a start-up of recruitment service for mature talent - Choo, Chern Ken (2024)
Malaysia is expected to become an aged society by 2044 with 14% of the population aged above 65. Only 45.2% of people aged 55-64 are employed, which is lower than other high-income economies. This aging trend would bring unique challenges to the nation especially in areas of employment, income security and aged care. The main aim of this start-up is to assist retirees in Malaysia in gaining access to a wide variety of job opportunities while allowing them to embrace active ageing. A survey was conducted through questionnaire to ascertain the employers' acceptance towards hiring of senior citizens in their organization, the willingness of retirees to return to the workforce. Internal and external analysis using PESTLE, Porter’s Five Forces, SWOT, TOWS, VRIO theories were conducted. Findings from primary research data show strong intention of working post-retirement among participants aged 50 and above. The result also shows participants’ acceptance of our platforms offering. Sales forecast and projection indicated the feasibility of the idea, and it is worthwhile exploring further.